? ?Antibacterial and Phytochemical Studies on Dicoma tomentosa: Short Communication - KHALID, S.; AFZA, N.; RIZVI, H.A.; BADAR, Y. (Biological Sciences - PJSIR, 1995)
The results represented in Table 1 indicate that a mild broad spectrum antibacterial activity was found in the extracts of flowers and roots of Dicoma tomentosa. Both flowers and roots at 1000 ug/ml cone. have completely inhibited all the tested strains of Shigella but have not shown activity against any Salmonella species.